Menstrual leave for female workers in Indonesia from the perspective of SDGs 3, 5, and 8 - Dhiyaa Thurfah Ilaa; Rona Agustin (Priviet Social Sciences Journal, 2026)
This study’s purpose is to explore the implementation of menstrual leave policy for female workers in Indonesia linked it through the perspective of Sustainable Development Goals, specifically goal 3 of SDG: Good Health & Well-Being, goal 5 of SDG: Gender Equality, and goal 8 of SDG: Decent Work & Economic Growth). Menstrual leave rights for female workers in Indonesia have been regulated by Law, however there are significant gaps on the implementation. By using qualitative approach through semi-structured interviews with female workers in Indonesia, this study identified four main themes: knowledge & awareness of menstrual leave rights, implementation variations of menstrual leave rights at workplaces, organizational culture & workplace support of women’s reproductive issues, and perception of productivity & appreciation of female workers. The results show that there is indeed a gap in the implementation of menstrual leave amongst the informants, with different reasons. The informants believe that menstrual leave can help with their physical and mental health, and built inclusivity and equality in their workplaces. This finding also confirms that for female workers in Indonesia, the support for their reproductive health at work can give positive contributions towards their work productivity.